Mixed-integer programming for control - Richards, A.; How, J. (2005 American Control Conference, 2005)
The article describes how mixed-integer programming (MIP) can be employed for feedback control. MIP can be used to find optimal trajectories subject to integer constraints, which can encode discrete decisions or nonconvexity, for example. This optimization can be performed online within model predictive control (MPC) to implement a feedback control law. The article discusses how to model systems using MIP, the implementation as a MPC, and techniques for fast solutions of the optimizations to make them suitable for real-time use.